Driving Lidl´s growth strategy in Portugal through customer loyalty: framing distribution in the implementation of a loyalty program - Viegas, Susana Margarida Fernandes (2022)
This Work Project aims to find a solutionfor a specific organizational challenge:increase Lidl’s average spending per ticket in Portugal. Despite having a similar number of buyers as the leading retailers, Lidlcustomersspend less amount on each trip.A literaturereview suggestedthat CustomerLoyalty isfundamental totackle thisissue,since it strengthenscommitment and rewards customersfor repeated and/or additional purchases. These insights were sustained by the survey questionnaire findings.Therefore, a Loyalty Programis the main recommendationfor solving the challenge.Following Lidl’s objective of increasing its customers’ average spending per ticket, this Work Project aims to explore the role of Place, which stands for distribution or convenient access, from the 5P’s of the Marketing Mix, in trying to achieve this goal. This study is inserted in a fictional Loyalty Program, which central element is a Loyalty Card. It starts with a benchmark analysis of the competitors’ distribution channels, and strategies for Lidl to implement its own program are suggested. Moreover, it is suggested a way of evaluating Place’s contribution in increasing loyalty and, consequently, the achievement of the firm’s goa